Effect of technology application in enhancing the weaknesses of market access, financial resources, and supplier resources on the aluminum industry - M.S. Mohamad Salleh; H. Vasudevan (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: A grasp of economic development is essential to comprehending policies and initiatives that support industrialization and the fight against poverty. It can assist in identifying areas for additional investment and growth and serve as a guide for planning, carrying out, and assessing economic development efforts. Bumiputera entrepreneurs encounter many obstacles to market accessibility, restricted financial means, and insufficient supplier networks, which may impede the expansion and prosperity of their businesses. The utilization of technology is essential in mitigating these shortcomings, allowing Bumiputera entrepreneurs to surmount obstacles and attain enduring prosperity in the aluminum sector. Entrepreneurs can create strong supplier networks, maximize the use of financial resources, and improve market access by utilizing technology. The purpose of this research is to examine how technology applications might mitigate the limitations of market access, financial resources, and supplier resources that impede the success of Bumiputera entrepreneurs in the aluminum sector. The growth and profitability of Bumiputera businesses can be inhibited by several obstacles, including restricted supplier networks, insufficient financial resources, and difficulty accessing markets.METHODS: The quantitative research approaches and methods can help provide a comprehensive understanding of the mediating effect of technology in enhancing market, finance, and supplier resource weaknesses for the success of Bumiputera entrepreneurs in the aluminum industry. An explanatory research design is a type of research design that focuses on the variables that determine the mediating effect of relationships and explains the causes and effects of the variables defining the phenomenon to be studied. The data was analyzed using SMART PLS3. The study was conducted specifically on Bumiputera entrepreneurs in the aluminum industry. Data from the Bumiputera aluminum industry was gathered through purposive sampling. As a minimal 75 sample size, a total of 80 questionnaires were distributed to Bumiputera respondents who have been working in the Malaysian aluminum industry. As a response, a 93.75% rate was achieved, and we dedicated a week in May 2023 to data collection.FINDINGS: Out of ten (10) hypotheses, only six (6) were valid, while the remaining four were ruled out. The recent high cases of the COVID-19 pandemic in 2019 have had an impact on them. The findings of this study contribute to the academic literature by highlighting the importance of technology in facilitating the success of Bumiputera entrepreneurs in the aluminum sector.CONCLUSION: The study empirically confirms and conceptually proves that the policies of industry associations and organizations (“Skim Jaminan Modal Kerja—Bumiputera”, the “Business Act 1956, and the Financial Procedure Act 1957) can advocate for policies that support Bumiputera entrepreneurs in accessing technology and improving their market access, financial resources, and supplier resources. The key technologies and strategies that help these entrepreneurs build thriving businesses offer recommendations for policymakers, business leaders, and entrepreneurs to support and promote success among this essential group of entrepreneurs. By lobbying for supportive policies, the industry can create an enabling environment for Bumiputera entrepreneurs to leverage technology effectively and overcome their weaknesses.